The role of high-dose corticosteroids in the treatment of chronic lymphocytic leukemia - Smolej, Lukáš (Expert opinion on investigational drugs, 2012)
INTRODUCTION: Management of refractory chronic lymphocytic leukemia (CLL) represents a major challenge because of the poor prognosis and limited treatment options. While corticosteroids have been used to treat CLL since 1940s, their benefit has never been conclusively proved. Recently, several groups reported use of high-dose corticosteroids (methylprednisolone or dexamethasone) either alone or combined with chemotherapy and/or monoclonal antibodies in relapsed/refractory CLL. AREAS COVERED: While efficacy of high-dose corticosteroids is excellent including responses in patients with bulky lymphadenopathy or those considered ultra high-risk CLL because of deletion and/or mutation of p53 gene, the duration of response is still unsatisfactory. Combination with monoclonal antibodies seems to improve therapeutic efficacy but no randomized trials have been conducted. For the purpose of this review, a search for terms, high-dose corticosteroids/methylprednisolone/dexamethasone, and chronic lymphocytic leukemia has been performed in PubMed and database of abstracts from American Society of Hematology Meetings. EXPERT OPINION: High-dose corticosteroids appear to play an important role in the management of highly pretreated relapsed/refractory CLL including patients with massive lymphadenopathy. Myelosuppression is usually limited but infectious toxicity, including increased risk of invasive fungal infections, represents the most dreaded side effects. This therapeutic approach should be further tested within large prospective trials, to optimize efficacy and safety.
Keywords: lidé; výsledek terapie; Drug Resistance, Neoplasm; chemorezistence; Mutation; vztah mezi dávkou a účinkem léčiva; Humans; protokoly protinádorové kombinované chemoterapie; Dose-Response Relationship, Drug; mutace; Genes, p53; geny p53; Glucocorticoids; zvířata; Animals; Treatment Outcome; glukokortikoidy; chronická lymfatická leukemie; Antineoplastic Combined Chemotherapy Protocols; Leukemia, Lymphocytic, Chronic, B-Cell